Bridges crossing fault rupture zones: A review. Issue 113 (October 2018) - Yang, Shuo; Mavroeidis, George P.
Abstract: Several earthquakes over the past two decades have demonstrated that bridges crossing fault rupture zones may suffer significant damage due to the combined effects of ground shaking and surface rupture. Although it is widely recommended to avoid building a bridge across a fault, it is not always possible to achieve this objective, especially in regions with a dense network of active faults. This review begins by compiling two databases: one of fault-crossing bridges damaged in past earthquakes and another of bridges crossing potentially active fault rupture zones. The article then continues to review findings of experimental, analytical and numerical studies, and to summarize seismic design provisions and recommendations related to fault-crossing bridges. The review ends with suggestions for future research directions in this area. Highlights: Information about fault-crossing bridges damaged in past earthquakes is collected. A database of well-documented cases of bridges crossing potentially active faults is compiled. Small- and large-scale experimental studies of fault-crossing bridges are reviewed. Analytical and numerical studies of bridges crossing fault rupture zones are summarized. Seismic design provisions and recommendations for fault-crossing bridges are discussed.